Chemical Composition and Cytotoxic Activity of Pistacia atlantica var. kurdica Fruits - A. Kaskoos, Raad; Javed Ahamad; Uthirapathy, Subasini (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
Pistacia atlantica var. kurdica (Anacardiaceae) is a major subspecies found in the Kurdistan region of Iraq and has several beneficial bioactivities such as antioxidant, antibacterial, and antiviral. P. atlantica growing in the Kurdistan region is not yet studied phytochemically and pharmacologically. Hence, the goal of the present study is to characterize chemical compounds present in ethanolic extract of P. atlantica fruits by gas chromatography–mass spectroscopy (GC–MS) and to evaluate cytotoxic activity using A549 (human lung cancer) cell lines by (3-4,5 dimethylthiazol-2yl2,5-diphenyl tetrazolium bromide) assay. The GC–MS analysis shows the presence of 33 chemical compounds which constitute about 99.95% of total compounds, and isospathulenol (14.63%), spathulenol (13.45%), α-terpineol (13.28%), limonene (10.92%), terpinolene (10.89%), β-myrcene (6.92%), ethyl pentadecanoate (6.15%), β-pinene (4.98%), and caryophyllene oxide (4.01%) were found as major chemical compounds. P. atlantica inhibits cell proliferation in A549 cell lines in a time (24 h) and dose-dependent manner (0.5–500 µg/mL). After 24 h of treatment with P. atlantica, the cell viability of A549 cell lines ranged from 93.01 ± 5.24 to 57.69 ± 4.15% for concentrations of 0.5–500 µg/mL, respectively. This study expands the knowledge of the chemical composition of P. atlantica fruits and provides scientific evidence for its possible use as an anticancer medicine. The substantial anticancer activity of P. atlantica fruits may be due to the presence of isospathulenol, spathulenol, α-terpineol, limonene, terpinolene, β-myrcene, ethyl pentadecanoate, β-pinene, and caryophyllene oxide.